Robust Metal Additive Manufacturing Process Selection and Development for Aerospace Components - Gradl, Paul; Tinker, Darren C.; Park, Alison; Mireles, Omar R.; Garcia, Marissa; Wilkerson, Ryan; Mckinney, Christopher (Journal of materials engineering and performance, 2022)
Metal additive manufacturing (AM) encapsulates the myriad of manufacturing processes available to meet industrial needs. Determining which of these AM processes is best for a specific aerospace application can be overwhelming. Based on the application, each of these AM processes has advantages and challenges. The most common metal AM methods in use include Powder Bed Fusion, Directed Energy Deposition, and various solid-state processes. Within each of these processes, there are different energy sources and feedstock requirements. Component requirements heavily affect the process determination, despite existing literature on these AM processes (often inclusive of input parameters and material properties). This article provides an overview of the considerations taken for metal AM process selection for aerospace components based on various attributes. These attributes include geometric considerations, metallurgical characteristics and properties, cost basis, post-processing, and industrialization supply chain maturity. To provide information for trade studies and selection, data on these attributes were compiled through literature reviews, internal NASA studies, as well as academic and industry partner studies and data. These studies include multiple AM components and sample build experiments to evaluate (1) material and geometric variations and constraints within the processes, (2) alloy characterization and mechanical testing, (3) pathfinder component development and hot-fire evaluations, and (4) qualification approaches. This article summarizes these results and is meant to introduce various considerations when designing a metal AM component.